Development and Democracy: Society, State, and Market in the Development Process - K.C., Ram Bahadur (Historical Journal, 2024)
This article tries to analyze the relationship between development and democracy from the vantage point of prior well-informed and substantive participation of stakeholders in development processes. It focuses on the processes of prior well-informed and substantive participation of stakeholders that are followed (or not followed) in the land development projects. Land development projects focus on accumulating stakeholders’ odd- or irregular-sized non-serviced parcels of land, and re-arrange them in smaller plots with road, drainage, open space, and other necessary infrastructure facilities. The issue of ‘development and democracy’ has been assessed from the dimensions of society, state, and market relations. Moreover, how the market is capitalizing on the situation created by the inadequate national policy as well as the ineffective roles of development agents have also been assessed.